Implications of initial physiological conditions for bacterial adaptation to changing environments. Issue 9 (23rd September 2020) - Heinemann, Matthias; Basan, Markus; Sauer, Uwe
Abstract : This piece discusses how the different observations of two independent studies (Kotte et al, 2014; Basan et al, 2020), regarding population‐level heterogeneity and lag times during diauxic shift, can be largely explained by different experimental protocols.